O ensino do futsal em um projeto de extensão: do plano à ação - Queiroz, Vitor Gabriel Batista (Universidade Federal de São Carlos, 2024)
Brazil, the country of football, which person should feel included and comfortable in the football universe. It is understood that based on practices and Game Pedagogy there is an advance as a tactic. Game Pedagogy is absorbed into an interactionist epistemology interrupted with the innatist and empiricist epistemologies, so that educational practice is adopted as a relational experience and not internalized within the subject as in the innatist or external to the subject as in the empiricist, which involves several social and educational practices towards a teaching objective. In view of the above, the present study aimed to investigate, based on the class plans and diaries prepared by the work team of the Academia ProFut extension project, the limits and pedagogical possibilities inscribed in the circumscribed field between the idealized and the realized. It was a cross-sectional, documentary, retrospective and thematic analysis study using the qualitative method. The research analyzed an academic extension project aimed at teaching football in a school located in a peripheral neighborhood of the city of São Carlos. This research analyzes in a chronological way comparing the lesson plans and the respective diaries of each class, of the 6th and 7th year classes, who attended the project in the morning (10:45 am to 12:15 pm), two days a week (Tuesday and Wednesday), after regular classes, with a time frame from 04/12/2022 to 05/25/2022, totaling 10 lesson plans and 10 consolidated class diaries. After analyzing the class plans and diaries prepared by the work team of the Academia Profut extension project, we identified the limits and pedagogical possibilities included, not circumscribed between the idealized and the realized, we can say that we identified the existence of educational processes, in regarding internal and external logic and also some limitations related to physical space and adaptation of the project to the school’s dynamics.
Teaching futsal in an extension project: from plan to action
La enseñanza del futsal en un proyecto de extensión: del plan a la acción
Keywords: Ensino do futsal; Projeto de extensão; Futebóis; Dialogicidade; CIENCIAS DA SAUDE::EDUCACAO FISICA